Cost-effectiveness Study in Type 2 Diabetes Mellitus in Asia: A Review - Wiracana, I Made; Priyatni, Nunung; Virginia, Dita Maria (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Type 2 Diabetes Mellitus (DM) requires intensive treatment to prevent progression and complications. One of the intensive treatments is insulin therapy. The increase in insulin price and variation in insulin therapy results in differences in treatment costs. In Asia, commonly used types of insulin therapy are NPH insulin and glargine insulin. It is urgent to define the most cost-effective insulin therapy among type 2 DM patients because of the economic burden.Objectives: This study aims to assess the cost-effectiveness of these insulin types. We did a narrative review using literature discussing the cost-effectiveness of insulin for type 2 DM patients.Methods: This study employs a narrative review approach using the PRISMA-P 2015 structured approach to examine studies. This article's methodological quality was evaluated using the Drummond checklist. The terms "cost-effectiveness analysis," "diabetes mellitus type 2," and "insulin" were used in the literature search for this study.Results: We obtained five pieces of literature fulfilling inclusion and exclusion criteria. The results indicated that the age range of type 2 DM patients in this study is 57-62 years, with a majority being women. The most frequently occurring complication is cardiovascular complications. NPH insulin and glargine insulin were the most extensively studied insulins in the literature review.Conclusion: Based on the cost-effectiveness analysis, glargine insulin is more cost-effective than NPH insulin in Asia due to the rare occurrence of hypoglycemia which is a common side effect as a treatment outcomes.